Thrombus in a normal sinus of Valsalva: angiographic, multiplane transoesophageal echocardiographic, and surgical findings. Issue 3 (September 1996) - Christiaens, L.; Allal, J.; Corbi, P.
Abstract : A large intraluminal thrombus within an otherwise normal sinus of Valsalva was diagnosed in a 41 year old man who was investigated for myocardial infarction. The thrombus was suspected by aortic root injection, confirmed by transoesophageal echocardiography, and treated surgically.